Surfactant-enhanced biodegradation of crude oil sludge in sequencing batch reactor: effect of surfactant concentration, oil loading rate and number of cycle per day - Kwanruethai Comchumpoo (Chulalongkorn University, 2014)
Thesis (M.S.) -- Chulalongkorn University, 2007